Cardiovascular Risk Factors in the Antiphospholipid Syndrome - Felipe Freire da Silva; Roger Abramino Levy; Jozélio Freire de Carvalho (Journal of Immunology Research)
A major cause of morbidity and mortality in the context of the antiphospholipid syndrome (APS) is the occurrence of thrombotic events. Besides the pathogenic roles of antiphospholipid antibodies (aPL), other risk factors and medical conditions, which are conditions for traditional risk of an individual without the APS, can coexist in this patient, raising their risk of developing thrombosis. Therefore, the clinical and laboratory investigation of comorbidities known to increase cardiovascular risk in patients with antiphospholipid antibody syndrome is crucial for the adoption of a more complete and effective treatment. Experimental models and clinical studies show evidence of association between APS and premature formation of atherosclerotic plaques. Atherosclerosis has major traditional risk factors: hypertension, diabetes mellitus, obesity, dyslipidemia, smoking, and sedentary lifestyle that may be implicated in vascular involvement in patients with APS. The influence of nontraditional risk factors as hyperhomocysteinemia, increased lipoprotein a, and anti-oxLDL in the development of thromboembolic events in APS patients has been studied in scientific literature. Metabolic syndrome with all its components also has been recently studied in antiphospholipid syndrome and is associated with arterial events.